"A Higher and Purer Shape": Kaufmann Kohler's Jewish Orientalism and the Construction of Religion in Nineteenth-Century America. Issue 3 (2019) - Goldstein, Evan
Abstract: This article uses the case of Kaufmann Kohler (1843–1926), an intellectual and institutional leader of American Reform Judaism, to explore the relationship between Orientalism and the category of religion in nineteenth-century America. Recent scholarship has shown that the lived religion of nineteenth-century American Jews departs significantly from the ideological hopes of Jewish elites. Connecting the emerging portrait of nineteenth-century Jewish laity with elite arguments for American Judaism, I reconsider Kohler's thought as a theological project out of step with his socioreligious milieu. Kohler is renowned for his theorizing of Judaism as a universal, ethical religion. As scholars have demonstrated repeatedly, defining Judaism as a "religion" was an important feature of Reform thought. What these accounts have insufficiently theorized, however, is the political context that ties the categorization of religion to the history of Orientalism that organized so many late nineteenth-century discussions of religion, Jewish and not. Drawing on work by Tracy Fessenden, John Modern, and Tisa Wenger, I show that Kohler's universal, cosmopolitan religion is a Jewish version of the Protestant secular. Like these Protestant modernists, Kohler defines Reform Judaism as a religion that supersedes an atavistic tribalism bound to materiality and ritual law. Being Jewish, for Kohler, means being civilized; reforming the soul of Judaism goes together with civilizing Jewish bodies and creating a Judaism that could civilize the world in an era in which religion and imperialism were overlapping interpretive projects with racial and gendered entanglements.